Optimization of ASTER Elevation Data to Improve Watershed Delineation - Akbari, Abolghasem; Fadzil, Mat Yahaya; Samah, Azizan Abu (2015)
The primary goal of this research is to examine the practical use of public domain satellite data in natural hazard modeling. Watershed delineation and characterization is one of the most important step in hydrological modeling. In last decade, considerable developments have been achieved for satellite industry, specifically in acquisition of terrain elevation data from the space. High resolution of digital elevation model (DEM) are now global freely available. The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) - Global DEM version 2 is one the pioneer source of elevation data available from October 2011. Optimization techniques were applied for ASTER-GDEM to improve watershed delineation and parameterizations in Muar watershed located in Peninsular Malaysia. The HEC-GeoHMS is employed to automate the watershed delineation and parametrization process. Result of this research shows that, DEM reconditioning by using complementary drainage network derived from google earth, significantly improve the watershed boundary delineation in flat and urban areas.